Building condition audit in public building case study at Majlis Bandaraya Shah Alam / Mohammad Amirul Ab Manaf - Ab Manaf, Mohammad Amirul (Faculty of Architecture , Planning and Surveying, 2015)
A building audit condition is a systematic approach to problem solving and decision making. The purpose of this research is to recommend for a better approach in inspecting and maintaining of a building to assess their suitability to meet community needs. While, the objectives of this research is to study the maintenance practise on the building audit condition at local authority, to identify the most common defect occurs at the public building and to determine the level of satisfaction of users in public building. This research is structured in six main chapters: (1) Introduction, (2) Literature review, (3) Research Methodology, (4) Case study, (5) Data analysis and lastly (6) Conclusion and recommendation. The scope of this research is focused on the building condition audit in public building at Shah Alam. We choose the three of public food court as the case study. Building condition audit is carried out to check the level of occupant satisfaction regarding the building condition and cleanliness. The research involves a distributing questionnaires surrounding at the area. The selections of respondent are limited among people around the area and department of building at local authority. At the same time we observe and inspect the building to find the common defect occur at the building. There are the several defects that occur in building such as dampness, crack, detach and other. The overall rating and interpretation states that the respondents are some agree with the local authority maintenance practice, while the condition and cleanliness is good and treated with care.